Repurposing metformin, simvastatin and digoxin as a combination for targeted therapy for pancreatic ductal adenocarcinoma. (28th October 2020) - Liu, Shi-He; Yu, Juehua; Creeden, Justin F.; Sutton, Jeffrey M.; Markowiak, Stephen; Sanchez, Robbi; Nemunaitis, John; Kalinoski, Andrea; Zhang, Jian-Ting; Damoiseaux, Robert; Erhardt, Paul; Brunicardi, F. Charles
Abstract: Patients with pancreatic adenocarcinoma (PDAC) have a 5-year survival rate of 8%, the lowest of any cancer in the United States. Traditional chemotherapeutic regimens, such as gemcitabine- and fluorouracil-based regimens, often only prolong survival by months. Effective precision targeted therapy is therefore urgently needed to substantially improve survival. In an effort to expedite approval and delivery of targeted therapy to patients, we utilized a platform to develop a novel combination of FDA approved drugs that would target pancreaticoduodenal homeobox1 (PDX1) and baculoviral inhibitor of apoptosis repeat-containing 5 (BIRC5) utilizing super-promoters of the target genes to interrogate an FDA approved drug library. We identified and selected metformin, simvastatin and digoxin (C3) as a novel combination of FDA approved drugs, which were shown to effectively target PDX1 and BIRC5 in human PDAC tumors in mice with no toxicity. Highlights: Identification of BIRC5 as therapeutic target. High throughput screening of FDA approved drugs using tumor specific super promoter reporter assay. Metformin, Digoxin and Simvastatin target PDX-1 and BIRC5. Metformin, Digoxin and Simvastatin synergistically anti-PDAC. Mechanism involves in C3 anti-PDAC.